Society Spotlight: European Commission-supported development of targeted nanomedicines: did MediTrans make a difference?. (July 2011) - Storm, G; Aime, S
Nanotechnology-inspired approaches to particle design and formulation, an improved understanding of (patho)physiological processes and biological barriers to drug targeting, as well as the limited input of new chemical entities in the ''pipeline'' of pharmaceutical companies, suggest a bright future for targeted nanomedicines as pharmaceuticals. There is an increased consensus to the view that a major limitation hampering the entry of targeted delivery systems into the clinic is that new concepts and innovative research ideas within academia are not being developed and exploited in close collaboration with the pharmaceutical industry. Thus, an integrated ''bench-to-clinic'' approach realized within a structural collaboration between industry and academia, will facilitate and promote the progression of targeted nanomedicines towards clinical application. The MediTrans project performed under the EU Framework Program 6, was designed to contribute to this ambition. The objectives of this collaborative initiative were: to apply nanotechnology for development of innovative targeted drug-delivery systems; to optimize targeted nanomedicines by using imaging guidance; to promote structural collaboration between industry and academia; and to forward targeted nanomedicines towards the clinic and the market. In this article, we will briefly address the research content, outcome and impact of the MediTrans project.